The Influence of Leadership, Talent Management, Organizational Culture and Organizational Support on Employee Engagement - Sadeli, Jimmy (Universitas Prasetiya Mulya, 2012)
A leadership-driven model was hypothesized to examine the simultaneous influences of three dimensions of leadershipbehaviors (transformational, transactional, and interaction between transformational and transactional) on employee engagement, mediated by three intangible organizational factors: (1) talent management practices, (2) organizational culture, and (3) perceived organizational support (POS). Results of this research show that leadership behaviors (transformational and interaction between transformational and transactional) significantly influence mediating variables (talent management practices, organizational culture and POS), whereas transactional leadership must interact with transformational leadership behavior to influence mediating variables. Both talent management practices and organizational culture influence employee engagement, while POS indirectly influences employee engagement.